Development of pH Meter with Solar Panel as Battery Replacement of Lithium Button Cell - Nor Khairina Batrisya Zul Khairi; Nur Aini Mohd Arish@Arshad (Progress in Engineering Application and Technology, 2022)
In 2011, it have been highly crucial for cost of solar energy device due to the limiting quantity of renewable energy supplies. Solar energy has a huge advantage over other traditional power generators in that even the tiniest photovoltaic (PV) solar cells can convert sunlight instantly into solar energy. The manufacture of lithium-ion batteries has resulted in greenhouse gas emissions, which have a negative influence on the environment. When compared to the usage of solar panels, which store solar energy to recharge the energy, the use of lithium batteries on pH meter devices can create pollution in terms of disposal. The objectives of this project are to establish a digital pH meter device with a solar panel and conduct a test to determine the device’s effectiveness. Comparison of the two types of battery are in category of durability, which is that lithium battery need to be replaced once the energy depleted. The result from the different types of batteries used are pretty much the same as the device used in this project is the same. It might be slightly different to each other as the method for the calibration may have an error during the process. The sample use is tap water have pH range of 6.56 to 6.63 which means it is near the range of neutral, which is 7. The recommendation for this device is to attach DC voltage booster or having the battery be attached with solar panel to execute a long run life cycle of the pH meter, as the solar panel will act as storage energy system and transmit the light energy into electrical energy.